Effect of Pre-germination seed treatments on germination of seeds and initial growth of Mango (Mangifera indica L) (Ghana Journal of Science, Technology and Development, 2020)
An experiment was conducted to find out the effects of some pre-germination seed treatments on germination of mango (Mangifera indica L.) seeds and initial growth of mango. Seeds obtained from a local mango variety at Nyankpala were sown in polyethylene bags filled with topsoil for the experiment. The four treatments used were; seeds sown without seed coats (SW), seeds without seed coats soaked in cool water of 5ÂºC for 12 hours before sowing (SSC), seeds without seed coats soaked in warm water of 15ÂºC for one minute before sowing (SSW) and seeds with seed coats sown to serve as the control (SC). Randomized Complete Block Design was used and each treatment was replicated three times. The parameters measured were germination percentage, height of seedlings, leaf length of seedlings, number of leaves and stem diameter of seedlings. Data obtained were analyzed using Analysis of Variance and the differences were determined by using Tukey-Kramer multiple comparison test. All the treated seeds recorded more than 80% of germination three weeks after sowing, with SSW recording the highest value of 91%. In general, the treated seeds performed significantly (p < 0.05) better than the control for the parameters studied. SSW is recommended for adoption since it performed optimally better than the other treatments in terms of number of leaves (7.67), leaf length (14.71 cm), leaf width (4.41 cm), stem diameter (1.82 cm) and plant height 20.86 cm).